Pengaruh Penambahan Pecahan Kulit Kemiri Sebagai Pengganti Sebagian Agregat Kasar Pada Beton Terhadap Massa Dan Kuat Tekan Beton - Dian Amri; Irwan Irwan (Universitas Medan Area, 2019)
Concrete is a material that is widely used and become a major element in the building. The advantages of concrete, among others, have a strong high pressure than the tensile strength, easily formed, does not require special care, the material is easy to obtain from the surrounding, and more durable than other building materials. The more concrete is used as the constituent material of the concrete, hence encouraging research to develop the material as well as the way of making concrete. Hazelnut shell is one type of particle that is very light weight in a dry and quite hard. Where the hazelnut shell is it self known as a lot of waste accumulated and tend to become garbage because its utilization is still small or relatively small, so it needs to be handled seriously. In addition, today hazelnut shell is only used for a small need only. The purpose of this research is to find out the compressive strength of concrete and to utilize the waste of hazelnut shell as 10%, 20% and 30% concrete additives with the planned K225 concrete quality, with 28 days concrete plan, The addition of hazelnut shell to the concrete mixture resulted decrease in compressive strength of normal concrete in each variation of the percentage. This is because the mixture of hazelnut shell is not strong enough to be a substitute for coarse aggregates, resulting in a decrease in the compressive strength of the concrete